From banks' strategies to financial (in)stability - Simone Berardi; Gabriele Tedeschi (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2015)
This paper aims to shed light on the emergence of systemic risk in credit systems. By developing an interbank market with heterogeneous financial institutions granting loans on different network structures, we investigate what market architecture is more resilient to liquidity shocks and how the risk spreads over the modeled system. In our model, credit linkages evolve endogenously via a fitness measure based on different banks strategies. Each financial institution, in fact, applies a strategy based on a low interest rate, a high supply of liquidity or a combination of them. Interestingly, the choice of the strategy in uences both the banks' performance and the network topology. In this way, we are able to identify the most effective tactics adapt to contain contagion and the corresponding network topology. Our analysis shows that, when financial institutions combine the two strategies, the interbank network does not condense and this generates the most efficient scenario in case of shocks.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: G01; G02; D85; 330; interbank market; dynamic network; fitness model; network resilience; bank strategy